Training- and contest-scheduling in endurance sports by means of course profiles and PerPot-based analysis - Perl, J.; Endler, S. (International Journal of Computer Science in Sport, 2006)
Scheduling of training and contcsts in outdoor endurance sports — e.g. running, biking, or skiing - is difficult through course contexts (ground condition, slopes etc) and delayed psychological reaction on load changes (see Figure 1). In the following, some of those impacts are exemplarily discussed for the case of running: Figure 2 shows the effect of delayed reaction on periodically changed speed on plain ground: From bottom to top, the first line contains the speed values (6.5 and 8.0 km/h), which are graphically reproduced as profile, followed by the corresponding heart rate profile and the heart rate maximum values in the top line. Figure 3 demonstrates, for the example of a periodic height profile (graphic on bottom), that the slope-caused load can affect the heart rate profile (graphic in the middle) more man the speed-cause load does (graphic on top). The red arrows mark phases of inverse proflies while the green arrows mark phases of equal tendencies. All examples are calculatcd on the basis of original data using the PerPot-derivate "SpeEdi Run". The aim of the paper is to demonstrate how a model-based analysis can help for predicting performance proflles in context-depending load situations and supporting load scheduling in contests.